FACTORS ANALYSIS FACTORS RELATED TO THE STADIUM OF CHRONIC KIDNEY FAILURE - Gustiawan, Ricki; Farich, Achmad; Muhani, Nova (LPPM STIKES Al-Ma'arif Baturaja, 2025)
Chronic Kidney Failure (CKD) is a condition in which there is a decrease in kidney function due to chronic and irreversible damage to the kidney parenchyma. The prevalence of CKF in the world in 2017 was 9.1% or around 70 million cases. Data from RSPBA as of December 31, 2023 was 2.5% (113 cases). Factors that play a role in the occurrence of CKF include a history of diabetes mellitus, hypertension, drug use, smoking, alcohol consumption, consumption of supplement drinks, and consumption of herbal medicine. The study aims to analyze factors related to the stage of CKF. The type of quantitative research with a cross-sectional approach. The population was 177 patients and a sample of 123 hemodialysis patients using a purposive sampling technique. The research period was March-July 2024. The data consisted of 2 collections, namely primary data obtained by questionnaires and interviews, then secondary data by observing medical records. Data analysis used for univariate analysis of frequency distribution, bivariate analysis using the chi square test. The results of the study showed that most of the 74% of patients with severe CKD had a history of diabetes mellitus (60.2%), hypertension (67.5%), use of drugs (71.5%), smoking (71.5%), alcohol consumption (66.7%), consumption of supplement drinks (77.2%), and consumption of herbal medicine (74.8%). The results of the bivariate test showed that there was a relationship between a history of diabetes mellitus, hypertension, consumption of supplement drinks, and consumption of herbal medicine with CKD (p<0.05) and there was no relationship between a history of drug use, smoking, alcohol consumption (p>0.05). It is expected that the hospital will strive to communicate and provide ongoing encouragement to patients, providing information related to risk factors for kidney failure so that behavior in preventing complications of kidney failure grows.